Unwrapping the Unknown: Exploring Novelty and Perceived Value as Mediators Between Uncertainty and Purchase Intention - Dimas Dimitralyani; Weni Novandari; Larisa Pradisti (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study investigates how uncertainty influences purchase intention for blind box products, with novelty and perceived value acting as mediating variables within the Stimulus–Organism–Response (S-O-R) framework. Utilizing a mixed-method approach, quantitative data were gathered from 128 Indonesian consumers of Blokees blind boxes through structured surveys, while qualitative insights were derived from interviews with experienced collectors. The findings reveal that uncertainty has a direct and significant effect on purchase intention and also indirectly enhances purchase behavior through its impact on novelty and perceived value. Novelty, defined as the consumer’s perception of newness and surprise, was found to stimulate emotional engagement and interest, while perceived value—comprising functional, emotional, and social dimensions, reinforced the overall utility and meaning of the product experience. All proposed hypotheses were statistically supported. The qualitative findings corroborate these results, highlighting emotional excitement, exploration, and social recognition as key psychological drivers in blind box consumption. The study contributes theoretically by confirming the psychological mechanisms underlying uncertainty-based marketing and provides practical guidance for marketers to design compelling surprise-driven consumer experiences.